Risk factors for the development of Spitz neoplasms. Issue 2 (21st February 2022) - Benton, Sarah; Roth, Andrew; Khan, Ayesha U.; Zhao, Jeffrey; Kim, Daniel; Compres, Elsy V.; Wagner, Annette M.; Kruse, Lacey L.; Zhang, Bin; Gerami, Pedram
Abstract: Background/Objectives: The principal environmental risk factor for conventional nevi and melanomas is ultraviolet exposure. However, little is known about genetic or environmental risk factors for developing Spitz tumors. This study investigates risk factors associated with Spitz neoplasms. Methods: Patients with Spitz tumors seen at Northwestern Memorial Hospital and Lurie Children's Hospital were surveyed with a 16‐item questionnaire about environmental and inherited factors. Spitz tumor patients were compared to a pediatric control cohort from a similar clinical setting. This was supplemented with a meta‐analysis of genetic and environmental causes of Spitz neoplasms. Results: One hundred and six Spitz and 58 control surveys were obtained and no statistically significant differences in genetic or environmental risk factors were found between Spitz and control groups. Conclusion: Our data and meta‐analysis suggest that typical risk factors associated with melanoma are not significantly associated with Spitz tumors. Identification of relevant genetic or environmental risk factors will likely require larger and population‐based studies.